WOMEN'S STRUGGLE IN THE NOVEL 'CHAAK': AN ANALYSIS - Mandal, Manisha; Singh, Sanjay Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A whole group of sensitive writers like the famous Hindi writer Maitreyi Pushpa feel that the country may have become independent on 15th August 1947, but women have not got freedom in the true sense. Even today they are fighting the battle of half the population on their own. From tribal life to villages and cities, from metropolises to metropolitan cities, the safety and respect of women is in the hands of men. They can become victims of sexual violence anywhere, be it in public places, workplace, while going to school or college. The female characters of Maitrayi Pushpa's novels not only declare war against this rigid, male chauvinistic system, but also emerge victorious. The novel 'Chaak' is a Gram Gandhi creation. In this novel, the joys and sorrows, happiness and sadness, festivals, economic challenges, social conflicts, caste hatred and the rapidly changing political equations of rural life have been depicted in an impressive manner. Just as the potter's wheel keeps rotating and creating new things, the wheel of time also keeps rotating and creating something new. 'Chaak' also tells the story of a dynamic village. In this creation, an attempt has been made to comprehensively depict the rapid changes taking place in the food habits, clothing, conduct, behaviour, economic activity, political awareness etc. of the people there. The exodus of talents in the country has become a nationwide problem. A chain has been formed for this. The migration from village to city and city to metropolis and again from metropolis to foreign countries is not only causing qualitative loss in terms of human resources, the increasing number of old age homes in cities is creating a different deep human crisis. Despite all this, it is not that easy for the kind-hearted villagers to get rid of sensitive issues like excessive love for villages, pain of separation from villages or their village in the nostalgia. For those illiterate or semi-literate people, whose roots are culturally connected to villages, villages are still both heaven and hell. In this regard, the author herself says- "Before you is the story of Atarpur village. A story created by imagination of those people who love their land so much that Atarpur is heaven and hell for them. The mutual relations, affection and loving behaviour of the farmers in every nook and corner of this village keep them connected to each other, while the natural jealousy, envy and surge of ambitions also keep them biting each other. In this way, the pulse of life remains constant in Atarpur.